Beyond Aid - Zoellick, Robert B. (World Bank, Washington, DC, 2017)
Robert B. Zoellick, President of the World Bank Group, spoke about leaving behind the past and facing today’s challenges squarely, constructively, and creatively. This is not the 1944 world that surrounded the creation of the Bank. Old models no longer fit current problems. The new “normal” will be dynamic, volatile, about countries earning their place, about lifting growth, about smart economic power, and about voice and social accountability. We must recognize that now we are all responsible stakeholders in an interdependent global economy. Zoellick spoke of what this new world means for development. Modern multilateralism heralds a world beyond aid. New policies are required. He advocated democratizing development so that all – North, South, East, West, rich and poor, men and women – can play a part in designing, executing, and continually improving development solutions. Openness, transparency, and accountability are key features – not only of the World Bank Group – but of government policy across the world. He proposed a Fifty Percent Solution, in which gender equality is smart economics. Releasing the full potential of half of the world’s population would truly democratize development.